2009
DOI: 10.1080/08946560802571870
|View full text |Cite
|
Sign up to set email alerts
|

Mistreatment of Older People in the United Kingdom: Findings from the First National Prevalence Study

Abstract: There have been few national studies of the prevalence of elder mistreatment (abuse and neglect) in private households. This article provides an overview of the UK National Prevalence Study of Elder Mistreatment that took place in 2006. It addressed 2,111 respondents in four countries who answered a face-to-face survey questionnaire. The achieved sample was weighted to be representative of the UK older population. Of respondents, 2.6% reported mistreatment by family members, close friends, or care workers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
7
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 8 publications
15
133
7
2
Order By: Relevance
“…It was consistent with the results of Biggs in the UK in a study entitled "Elder Abuse Varies With Economic and Health Status" (22), and Li Wu in China in a study entitled "Having Demanding Difficult Jobs and Only Relying on One's Income Are the Risk Factors for Abuse" (23).…”
Section: Discussionsupporting
confidence: 78%
“…It was consistent with the results of Biggs in the UK in a study entitled "Elder Abuse Varies With Economic and Health Status" (22), and Li Wu in China in a study entitled "Having Demanding Difficult Jobs and Only Relying on One's Income Are the Risk Factors for Abuse" (23).…”
Section: Discussionsupporting
confidence: 78%
“…Retrospective studies always present several clear shortcomings, but when it comes to the prevalence of abuse and the association between abuse and ill health, they are to date essentially the only method that has been used 10,14,36 . Even so, it is also plausible that ill health e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that severe abuse among women and men declines with age 3,[7][8][9][10]30 . Elderly have a reduced risk of being personally abused, yet they still have a high degree of fear of crime 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This is a shared finding from research on abuse of children, adults and older adults Cambridge et al (2006); Biggs et al (2009);Campbell-Reay & Browne (2001);McCarthy & Thompson (1996). (Tiffany, 1890;Gollaher, 1995).…”
Section: Background To the Legislationmentioning
confidence: 99%